Corrigendum: Complement activation via the lectin and alternative pathway in patients with severe COVID-19(Front. Immunol., (2022), 13, (835156), 10.3389/fimmu.2022.835156) - Niederreiter, Janina; Eck, Christine; Ries, Tajana; Hartmann, Arndt; Märkl, Bruno; Büttner-Herold, Maike; Amann, Kerstin Ute; Daniel, Christoph (Frontiers in Immunology, 2023)
In the published article, information in the Acknowledgments was mistakenly not included in the publication. A correction has been made to Acknowledgments:
CRIS-Team Scopus Importer:2023-10-20
Keywords: autopsy; complement deposition; COVID-19; kidney; lectin pathway; lung